Quantification of Bacterial Colonization in Dental Hard Tissues Using Optimized Molecular Biological Methods - Sterzenbach, Torsten; Pioch, Anne; Dannemann, Martin; Hannig, Christian; Weber, Marie-Theres (Frontiers in Genetics, 2020)
Bacterial infections of root canals and the surrounding dental hard tissue are still a challenge due to biofilm formation as well as the complex root canal anatomy. However, current methods for analyzing biofilm formation, bacterial colonization of root canals and dental hard tissue (e.g. scanning electron microscopy, confocal laser scanning microscopy (CLSM) or determination of colony forming units (CFU)) are time-consuming and only offer a selective qualitative or semi-quantitative analysis. The aim of the present study is the establishment of optimized molecular biological methods for DNA-isolation and quantification of bacterial colonization via quantitative PCR (qPCR) from dental hard tissue. Root canals of human premolars were colonized with Enterococcus faecalis. For isolation of DNA, teeth were then grinded with a cryo mill. Since the hard tissues dentin and especially enamel belong to the hardest materials in the human organism, the isolation of bacterial DNA from root dentin is very challenging. Therefore, treatment steps for the isolation of DNA from grinded teeth were systematically analyzed to allow improved recovery of bacterial DNA from dental hard tissues. Starting with the disintegration of the peptidoglycane-layer of bacterial cells, different lysozyme solutions were tested for efficacy. Furthermore, incubation times and concentrations of chelating agents such as EDTA were optimized. These solutions are crucial for the disintegration of teeth and hence improve the accessibility of bacterial DNA. The final step was the determination of prior bacterial colonization of each root canal as determined by qPCR and comparing the results to alternative methods such as CFU. As a result of this study, optimized procedures for bacterial DNA-isolation from teeth were established, which result in an increased recovery rate of bacterial DNA. This method allows a non-selective and straightforward procedure to quantify bacterial colonization from dental hard tissue. It can be easily adapted for other study types such as microbiome studies and for comparable tissues like bones.